0
$\begingroup$

I was faced with a problem about evaluating limits.

I know for a fact that when a limit is indeterminate when substituted with the value $x$ is approaching, I differentiate by L'Hopital's Rule. But then my professor said that it was for higher Math that I should "manually" evaluate the limits. Is there any step-by-step procedure on how to do this? An example is cited below: $$\lim\limits_{x\to 1}\frac{x^{10}-1}{\sqrt x-1}.$$

By the use of differentiation, I got $20$ as the answer. But how can I show the answer without differentiation? I tried rationalizing the denominator but it ends up with $0$ as the answer. I have also tried to factor the denominator after rationalizing by $(x)^3-(1)^3$ but still it's the same dead end.

$\endgroup$
  • $\begingroup$ Hint: Let $y=\sqrt{x}$, and note that $(y^{20}-1)/(y-1)=y^{19}+y^{18}+\cdots +1$. $\endgroup$ – André Nicolas Feb 11 '16 at 11:25
  • $\begingroup$ You can use the standard limit $\lim\limits_{x \to a}\dfrac{x^{n} - a^{n}}{x - a} = na^{n - 1}$ and get the answer simply by dividing the numerator and denominator by $(x - 1)$. $\endgroup$ – Paramanand Singh Feb 11 '16 at 16:09
3
$\begingroup$

Hints:

(1) $$x^{10} - 1 = (x - 1)(x^9 + x^8 + x^7 + x^6 + x^5 + x^4 + x^3 + x^2 + x + 1)$$

(2) $$\sqrt{x} - 1 = \frac{x - 1}{\sqrt{x} + 1}$$

Can you take it from here?

$\endgroup$
  • $\begingroup$ ooh i think i can =) thank you =D $\endgroup$ – user312617 Feb 11 '16 at 11:27
2
$\begingroup$

Set $u=\sqrt x$. Then $$\frac{x^{10}-1}{\sqrt x-1}=\frac{u^{20}-1}{u-1}\to(u^{20})'\Big\vert_{u=1}=20.$$

$\endgroup$
2
$\begingroup$

$\lim_{x\to1} \frac{x^{10}-1}{\sqrt{x}-1} = \lim_{x\to1} \frac{\sqrt{x}^{20}-1}{\sqrt{x}-1}= \lim_{x\to 1} (\sqrt{x}^{19}+\sqrt{x}^{18}+...+\sqrt{x}+1 )= 20$

$\endgroup$
1
$\begingroup$

You should cancel out the terms to get rid of $\frac{0}{0}$ situation. Observe that \begin{equation} x^{10}-1=(x-1)(x^9+\dots+1) \end{equation} Hence \begin{equation} \frac{x^{10}-1}{\sqrt{x}-1}=\frac{(x-1)}{\sqrt{x}-1}(x^9+\dots+1)=)(\sqrt{x}+1)(x^9+\dots+1) \end{equation} The right hand side is now simple to evaluate as $x\rightarrow 1$ in particular it is equal to $20$.

$\endgroup$
  • $\begingroup$ nice! thanks for the info on x^10-1 i think my problem has been solved thanks =D $\endgroup$ – user312617 Feb 11 '16 at 11:28
  • $\begingroup$ may i ask how x^10−1=(x−1)(x^9+⋯+1) was derived? Just for my learning when I come across this again =) $\endgroup$ – user312617 Feb 11 '16 at 11:52
1
$\begingroup$

Alternative: Set $u=\sqrt x-1$, then $$ x^{10}-1=(1+u)^{20}-1=1+20u+\sum_{k=2}^{20}\binom{20}k u^k -1 \\=u·\left(20+u·\sum_{k=2}^{20}\binom{20}k u^{k-2}\right) $$ which avoids collecting the 20 limits to 1 in the geometric sum formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.